Does the gender composition of forest and fishery management groups affect resource governance and conservation outcomes: A systematic map protocol - Leisher, C.; Temsah, G.; Booker, F.; Day, M.; Agarwal, B.; Matthews, E.; Roe, D.; Russell, D.; Samberg, L.; Sunderland, Terry C.H.; Wilkie, D. (Springer, 2015)
In the fields of environmental governance and biodiversity conservation, there is a growing awareness that gender has an influence on resource use and management. Several studies argue that empowering women in resource governance can lead to beneficial outcomes for resource sustainability and biodiversity conservation. Yet how robust is the evidence to support this claim? Here we focus on the forestry and fisheries sectors to answer the primary question: What is the evidence that the gender composition of forest and fishery management groups affects resource governance and conservation outcomes? Our objective is to produce a systematic map of the evidence highlighting, inter alia, the geographic distribution and quality of the evidence, the consistency and robustness of the findings, and where further research is needed.